Incremental prognostic value of biomarkers beyond the GRACE (Global Registry of Acute Coronary Events) score and high-sensitivity cardiac troponin T in non-ST-elevation acute coronary syndrome - Widera, Christian; Pencina, Michael J; Bobadilla, Maria; Reimann, Ines; Guba-Quint, Anja; Marquardt, Ivonne; Bethmann, Kerstin; Korf-Klingebiel, Mortimer; Kempf, Tibor; Lichtinghagen, Ralf; Katus, Hugo; Giannitsis, Evangelos; et al. (Clinical chemistry, 2013)
Guidelines recommend the use of validated risk scores and a high-sensitivity cardiac troponin assay for risk assessment in non-ST-elevation acute coronary syndrome (NSTE-ACS). The incremental prognostic value of biomarkers in this context is unknown.We calculated the Global Registry of Acute Coronary Events (GRACE) score and measured the circulating concentrations of high-sensitivity cardiac troponin T (hs-cTnT) and 8 selected cardiac biomarkers on admission in 1146 patients with NSTE-ACS. We used an hs-cTnT threshold at the 99th percentile of a reference population to define increased cardiac marker in the score. The magnitude of the increase in model performance when individual biomarkers were added to GRACE was assessed by the change (Δ) in the area under the receiver-operating characteristic curve (AUC), integrated discrimination improvement (IDI), and category-free net reclassification improvement [NRI(>0)].Seventy-eight patients reached the combined end point of 6-month all-cause mortality or nonfatal myocardial infarction. The GRACE score alone had an AUC of 0.749. All biomarkers were associated with the risk of the combined end point and offered statistically significant improvement in model performance when added to GRACE (likelihood ratio test P ≤ 0.015). Growth differentiation factor 15 [ΔAUC 0.039, IDI 0.049, NRI(>0) 0.554] and N-terminal pro-B-type natriuretic peptide [ΔAUC 0.024, IDI 0.027, NRI(>0) 0.438] emerged as the 2 most promising biomarkers. Improvements in model performance upon addition of a second biomarker were small in magnitude.Biomarkers can add prognostic information to the GRACE score even in the current era of high-sensitivity cardiac troponin assays. The incremental information offered by individual biomarkers varies considerably, however.
Gesehen am 04.11.2021